A STUDY TO ROLE OF CUCURBITACEAE FAMILY IN BRYONIA ALBA WITH ITS MEDICINAL USES - DR. SURESHBABU (Global Journal of Plant and Soil Sciences, 2025)
The Cucurbitaceae is a medium sized and botanical highly specialized family of mainly climbing plants. It is of major importance to man as a source of foods. The climbing plants have palmately veined leaves, unisexual flowers with yellowish petals and climb by means of spiraling tendrils. Bryonia Alba is a vigorous wine in the family cucurbitaceae. Colocynth, bitter apple, is a fruits bearing plant for cucurbitaceae family.